Bitumen binders for the climatic conditions of Jordan from the point of view of the temperature range of road operation - Atout Hassan Abdellatif tahsin; Ya. M. Katrich; M. A. Vysotskaya (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. The road network, its qualitative and quantitative state, is an indicator of the socio-economic development of any country. The climatic characteristics of the Middle East and, specifically, Jordan, impose a number of stringent requirements on the physicomechanical properties of asphalt concrete mixtures and the operational characteristics of asphalt concrete in pavement, such as rut resistance and fatigue resistance. These issues are particularly acute in countries with a dry climate. By using an approach to the selection of bitumen binders based on the actual range of road operation, it is possible to minimize the occurrence of early defects on the pavement. The aim of this study was to zone the regions of the country based on climatic characteristics, calculate the actual PG grades of bitumen binders for these regions, which would reflect the real temperature range of asphalt concrete operation in the pavement and allow for the reduction of the intensity of plastic deformations, rutting, and temperature-cracking on the roads of Jordan.Method. The implementation of the set goal was done through the analysis of the climatic conditions of all available settlements in Jordan, with the collection of a temperature array over 15 years on a daily basis throughout the year, and the calculation of actual pavement operating temperatures during the hottest and coldest periods using a standard methodology.Result. The minimum allowable PG grades of bitumen binders for use in the structural layers of Jordan's road pavement were calculated. Based on the analysis of the country's climatic conditions and the performed calculations, a zoning map of Jordan was proposed according to the PG grades of bitumen binders.Conclusion. The question of Jordan's road engineers fully transitioning to the Superpave system is ambiguous, however, the use of bitumen binders in the technology of preparing asphalt concrete mixtures with the actual range of operating temperatures will allow for a significant leap in increasing the intervals between road repairs. When developing formulas for PG grades of bitumen binders in laboratory conditions, it is advisable to use modifiers such as rubber powder, SBS polymers, EVA, wax, as well as their complex combination.